Targeting cereblon in hematologic malignancies. (January 2023) - Fuchs, Ota
Abstract: The protein cereblon (CRBN) is a substrate receptor of the cullin 4-really interesting new gene (RING) E3 ubiquitin ligase complex CRL4 CRBN . Targeting CRBN mediates selective protein ubiquitination and subsequent degradation via the proteasome. This review describes novel thalidomide analogs, immunomodulatory drugs, also known as CRBN E3 ubiquitin ligase modulators or molecular glues (avadomide, iberdomide, CC-885, CC-90009, BTX-1188, CC-92480, CC-99282, CFT7455, and CC-91633), and CRBN-based proteolysis targeting chimeras (PROTACs) with increased efficacy and potent activity for application in hematologic malignancies. Both types of CRBN-binding drugs, molecular glues, and PROTACs stimulate the interaction between CRBN and its neosubstrates, recruiting target disease-promoting proteins and the E3 ubiquitin ligase CRL4 CRBN . Proteins that are traditionally difficult to target (transcription factors and oncoproteins) can be polyubiquitinated and degraded in this way. The competition of CRBN neosubstrates with endogenous CRBN-interacting proteins and the pharmacology and rational combination therapies of and mechanisms of resistance to CRL4 CRBN modulators or CRBN-based PROTACs are described.